소음저감형 시스템 알루미늄 거푸집의 최적 개념디자인 선정 - 홍종현; 염동준; 김영석; Hong, Jong Hyun; Yeom, Dong Jun; Kim, Young Suk (한국건설관리학회 논문집, 17(2), 2016)
In Korea, a series of noise-reduced aluminum forms are being recently used in apartment housing construction. However, their complicated and time-consuming work processes, and the noise which is still generated due to the inherent property of aluminum when especially installing and dismantling them have been pointed out as a problem to be certainly solved for increasing their practical use in construction sites. The primary objectives of this study are proposing an optimal conceptual design of a newly designed noise-reduced aluminum form and verifying the technical feasibility by conducting a working mock-up drive experiment. Thus, conventional noise-reduced aluminum forms have been analyzed and three conceptual designs of a newly noise-reduced aluminum forms have been deducted. AHP has been applied to a survey data collected by interviewing field experts. A trade-off analysis results have shown that 'Noise-reduced System Aluminum Form with a Drop-down Floor Post and Adaptive Beam' the highest weights of safety(0.52), work convenience(0.54) and thus selected. The suggested conceptual design in this study improved problems of conventional system aluminum forms. It is also expected that the suggested design will be used as a reliable guideline for the actual development of an aluminum form that ensures noise-reduce, work convenience and labor safety. 최근 국내 공동주택 골조공사에 있어서 소음저감형 알루미늄 거푸집의 활용이 증가하고 있다. 그러나 현재까지 개발된 소음저감형 알루미늄 거푸집은 복잡한 작업프로세스로 인해 작업 생산성이 저하되고, 특히 설치 해체 작업 시 알루미늄의 물성으로 인해 발생하는 소음을 여전히 방지하지 못한다는 문제점을 지니고 있다. 따라서 본 연구의 목적은 새로운 소음저감형 알루미늄 거푸집의 최적 개념디자인을 제안하고, 최적 개념디자인을 토대로 제작된 워킹목업(Working Mock-up)의 기술적 타당성을 검토하는 것이다. 이를 위해 본 연구에서는 기존 알루미늄 거푸집의 분석을 통해 새로운 형태의 소음저감형 알루미늄 거푸집 개넘디자인 3개 안을 도출하였으며, 현장 전문가 설문조사를 통해 AHP 분석을 수행하였다. AHP 분석 기법을 활용하여 Trade-off Analysis를 수행한 결과, 안전성(0.52)과 작업편의성(0.54) 부분에서 가장 높은 가중치 값이 도출된 '드롭다운 동바리와 가변빔이 적용된 소음저감형 시스템 알루미늄 거푸집'이 최적 개념디자인으로 선정되었다. 본 연구를 통해 도출된 소음저감형 알루미늄 시스템 거푸집의 최적 개념디자인은 기존 소음저감형 시스템 거푸집의 문제점을 해결하고, 실질적인 소음저감은 물론 작업 편의성 및 노무자의 안전성이 제고된 실제 소음저감형 알루미늄 거푸집의 개발에 활용될 수 있을 것으로 기대된다.